Investigation of Usability of Sepiolite as a Pozzolan in Production of High Performance Cementitious Composites - Serkan Subaşı; Rasim Cem Saka (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The continuous growth of population and urbanization in the world significantly increases the demand for cement. In terms of sustainability, the cement industry needs to develop new and effective pozzolans with the appropriate recycling of alternative raw materials. It is also important to evaluate sepiolite, which has very limited resources in the world compared to other industrial minerals and whose economic deposits are limited to Spain and Türkiye. In this study, the usability of sepiolite as a pozzolan in cement and its effects on physical, mechanical and durability properties were investigated. First of all, the chemical and physical properties of sepiolite in Eskisehir region were investigated. Crude and ground sepiolite calcined at 500 ºC, 700 ºC and 900ºC were substituted for CEM I 42.5 R class standard Portland cement at 5-10-15% and 20% ratios. The pozzolanic activities of produced sepiolite substituted cement were determined according to ASTM C-311. As a result, crude sepiolite retains more water than calcined sepiolite, thus negatively affecting the strength properties of the concrete. Additionally, sepiolite is considered suspicious (harmful-harmless) in terms of alkali silica reactivity except 10%-15%-20% crude sepiolite substitutions. Overall, It has been observed that sepiolite does not have sufficient pozzolanic properties in cementitious composites.